The association of nonalcoholic fatty liver disease with genetic polymorphisms: a multicenter study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Introduction Growing evidence suggests that multiple factors, such as insulin resistance, nutritional factors, gut microbiota, and hormones released from the adipose tissue, act together on genetically predisposed individuals. We aimed to investigate whether various single-nucleotide polymorphisms (SNPs) play a role in the development of nonalcoholic fatty liver disease (NAFLD) and severity of liver damage in the Anatolian population. Methods Two hundred and sixteen patients with biopsy-proven NAFLD and 150 control participants, aged 18-70 years, were consecutively enrolled in this multicenter study. Blood samples were genotyped for the PNPLA3 (rs738409), IL28B (rs12979860, rs12980275, rs8099917), PPAR- 227 ALA, PPAR- pro 12 ALA, SOD2 C47T, and LOX-1 IVS4-14 polymorphisms using the custom-made LightSNiP assays on a LightCycler 480 II instrument. Results Genotypic distributions of PNPLA3 rs738409 SNPs were different between NAFLD and control participants, but not for other SNPs. The PNPLA3 rs738409 GG polymorphism was associated with a 27-fold increased risk of development of NAFLD (odds ratio=27.8, 95% confidence interval: 3.5-218.4; P=0.002). Patients with the PNPLA3 GG genotype had higher nonalcoholic fatty liver disease activity score levels compared with patients with the PNPLA3 CC genotype (P<0.005). NAFLD patients without fibrosis had a higher frequency of IL28B rs12979860 TT and rs12980275 GG genotypes compared with NAFLD patients with fibrosis (P<0.005). Conclusion The present study proposes that polymorphisms in the PNPLA3 gene have highly predictive value in the development of NAFLD and are independently associated with the severity of liver histology in patients with NAFLD. The results of this study suggest that IL28B rs12979860 TT or rs12980275 GG may play an important protective role against the development of advanced fibrosis and even cirrhosis. Copyright (C) 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: genetic polymorphism; interleukin 28B; nonalcoholic fatty liver disease; patatin-like phospholipase domain-containing protein 3; DENSITY-LIPOPROTEIN CHOLESTEROL; ACTIVATED RECEPTORS ALPHA; CHRONIC HEPATITIS-C; DOMAIN-CONTAINING 3; INSULIN-RESISTANCE; GAMMA2 POLYMORPHISMS; I148M VARIANT; PNPLA3; RISK; SUSCEPTIBILITY